THE IMPACT OF AI TECHNOLOGIES IN MODERN HEALTHCARE: A CRITICAL ANALYSIS OF CHALLENGES, OPPORTUNITIES OF FUTURE PROSPECTS (The Research of Medical Science Review, 2025)
This study critically evaluates the transformative role of artificial intelligence (AI) technologies within contemporary healthcare systems, drawing upon an extensive synthesis of current literature and empirical case studies. The investigation highlights the integration of AI-driven tools across clinical and administrative domains, where these technologies are increasingly deployed to support diagnostic accuracy, optimize therapeutic interventions, and streamline operational workflows. Notably, leading healthcare institutions have adopted AI-enabled solutions to complement human expertise in disease detection, treatment planning, and patient monitoring, thereby enhancing both clinical outcomes and institutional efficiency. Beyond clinical settings, AI applications are also reshaping nursing practices and healthcare management through automation, predictive analytics, and resource optimization. While the integration of AI into healthcare delivery is largely perceived as a paradigm shift towards innovation and efficiency, it simultaneously presents multifaceted challenges including ethical dilemmas, data governance issues, algorithmic bias, and systemic resistance to technological change. This study articulates a balanced discourse, juxtaposing the emergent opportunities presented by AI with the socio-technical and regulatory complexities that may impede its adoption. In projecting the trajectory of AI in healthcare, the paper underscores the imperative for strategic frameworks, robust policy development, and interdisciplinary collaboration to fully harness AI's potential. Future integration will necessitate not only technological sophistication but also institutional readiness and policy foresight to ensure equitable, ethical, and effective deployment across health systems.